Diagnosis and Treatment of Small Intestinal Bacterial Overgrowth - Toman Nababan; Achmad Fauzi (The Indonesian Society for Digestive Endoscopy, 2015)
Small Intestinal Bacterial Overgrowth (SIBO) is a clinical condition, in which excess amounts of bacteria are found in small intestine. SIBO occurred when normal homeostatic mechanism which control enteric bacteria population disrupted. Elderly patients are more vulnerable to SIBO which can be caused by two conditions, which are gastric acid reduction and disproportionately drugs consumption which then caused hypomotility. There are several methods to diagnose SIBO, but diagnose often begin with suspicion and history of risk factors of SIBO. There are two most frequent tests in SIBO diagnostic, which are bacterial culture examination and breath test. Treatments of SIBO are: (1) Treatment of underlying disease and improvement of medical condition; (2) Eradication of excess bacterial growth; (3) Resolve nutritional deficiencies which related to SIBO.